2021
DOI: 10.3390/mi12080973
|View full text |Cite
|
Sign up to set email alerts
|

Bandwidth Broadening of Piezoelectric Energy Harvesters Using Arrays of a Proposed Piezoelectric Cantilever Structure

Abstract: One of the most important challenges in the design of the piezoelectric energy harvester is its narrow bandwidth. Most of the input vibration sources are exposed to frequency variation during their operation. The piezoelectric energy harvester’s narrow bandwidth makes it difficult for the harvester to track the variations of the input vibration source frequency. Thus, the harvester’s output power and overall performance is expected to decline from the designed value. This current study aims to solve the proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…According to the literature [45], connecting different energy harvesting cantilever beams of the same thickness but with different lengths, can produce higher output power. It was reported that the output power was increased from 2 µW to 5 µW, and the bandwidth was widened from (47, 55) Hz to (22,88) Hz. Therefore, in this study, we decided to use the same thickness but different length cantilevers.…”
Section: Finite Element Analysis Of Multiresonant Piezoelectric Energ...mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature [45], connecting different energy harvesting cantilever beams of the same thickness but with different lengths, can produce higher output power. It was reported that the output power was increased from 2 µW to 5 µW, and the bandwidth was widened from (47, 55) Hz to (22,88) Hz. Therefore, in this study, we decided to use the same thickness but different length cantilevers.…”
Section: Finite Element Analysis Of Multiresonant Piezoelectric Energ...mentioning
confidence: 99%
“…In the literature, the piezoelectric effect is among, if not the first, most employed principle in the field of mechanical micro energy conversion [13][14][15]. Based on the "direct piezoelectric effect" phenomenon that is also employed in sensors [16] and self-sensing actuators [17,18] for further feedback control [19][20][21][22], piezoelectric energy harvesting devices can scavenge the energy from vibrations and motion present in the surroundings to provide the maximum output voltage when operating at their resonance frequencies. However, exciting the devices at their resonance frequencies is challenging because the available surrounding frequency is generally low whilst the resonance of the harvester's structure is high.…”
Section: Introductionmentioning
confidence: 99%
“…Piezoelectric transductions commonly consist of a cantilever beam on which one or more piezoelectric are embedded. For example, in Salem et al (2021), a single-beam piezoelectric cantilever structure has been investigated, in which to achieve a fixed output power and bandwidth, the total length of piezoelectric material and the cantilever beam length of the structure have been set to constant values. In Borowiec (2015), an energy harvester system is proposed, which consisted of a cantilever beam with a tip mass and piezoelectric patches.…”
Section: Introductionmentioning
confidence: 99%
“…Wang [25] determined the relationship between the thickness of the beam and the output power of the energy harvester through theory and experiments. Salem [26] divided the piezoelectric material of the straight beam piezoelectric energy harvester into n segments to widen the frequency and improve the output power.…”
Section: Introductionmentioning
confidence: 99%